Spiritualitas dalam Ruang Cyber (Cyberspace): Makhluk Digitalis sekaligus Spiritualis - Frets Keriapy; Yoel Giban; Tinus Giban (Tumou Tou, 2022)
The development of technology is so massive, that humans are no longer called only social and spiritual beings, but there is a new label attached to humans, namely digital beings (homo digitalis). This label is given because of seeing the human condition that is so active not only in the reality of the social environment, but also in the virtual reality environment. By using descriptive analysis which is part of the literature research method, the author analyzes the humans condition in the digital era. Not only is it socially useful to grow - in this case, there is another social space that is virtual - but also in this digital era, the opportunity to use every available platform to spread the Gospel of God's Kingdom. Humans, who are digital and spiritual beings, seek identity and spiritual nourishment not longer in church buildings but also on every platform provided in cyberspace. Therefore, churches that are only busy closing themselves in and do not participate in using social media as an evangelistic platform will be left behind.